PENERAPAN KONSEP SILBERMAN DALAM METODE CERAMAH PADA PEMBELAJARAN PAI - Jon Helmi (AL-ISHLAH: Jurnal Pendidikan, 2016)
“Metode Ceramah” can be defined as a way of presenting the lesson through oral or explanation directly to a group of students.“Metode ceramah” is a method that use until today by any teacher or instructor. “Metode Ceramah” on the subjects of Islamic Religion Education (PAI) has not been so appropriate. It just looks teacher center, while students are not active in their learning and tend to be lazy. This paper aims to apply the concept of Melvin on “metode ceramah” that can create original learning that is passive to active and improve student achievement. Melvin concept to effective teaching with “Metode Ceramah” is to arouse interesting, to maximize comprehension and recall, involving students during lectures, and reinforce what has been delivered.